2021
DOI: 10.1186/s12977-021-00548-2
|View full text |Cite
|
Sign up to set email alerts
|

Vpx enhances innate immune responses independently of SAMHD1 during HIV-1 infection

Abstract: Background The genomes of HIV-2 and some SIV strains contain the accessory gene vpx, which carries out several functions during infection, including the downregulation of SAMHD1. Vpx is also commonly used in experiments to increase HIV-1 infection efficiency in myeloid cells, particularly in studies that investigate the activation of antiviral pathways. However, the potential effects of Vpx on cellular innate immune signaling is not completely understood. We investigated whether and how Vpx aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…2C). However, we cannot rule out that Vpx influences other aspects of myeloid cell biology unseen here, which may include alterations in interferon signaling, NF-κB activity, and gene silencing (Chougui et al, 2018;Cingoz, Arnow, Puig Torrents, & Bannert, 2021;Fink et al, 2022;Yurkovetskiy et al, 2018). Nevertheless, genetic modification of MDDCs through lentiviral-mediated gene delivery can be a useful tool for testing hypotheses related to cell activation, virus infection, and cell-cell communication.…”
Section: Understanding Resultsmentioning
confidence: 89%
“…2C). However, we cannot rule out that Vpx influences other aspects of myeloid cell biology unseen here, which may include alterations in interferon signaling, NF-κB activity, and gene silencing (Chougui et al, 2018;Cingoz, Arnow, Puig Torrents, & Bannert, 2021;Fink et al, 2022;Yurkovetskiy et al, 2018). Nevertheless, genetic modification of MDDCs through lentiviral-mediated gene delivery can be a useful tool for testing hypotheses related to cell activation, virus infection, and cell-cell communication.…”
Section: Understanding Resultsmentioning
confidence: 89%
“…However, optimization of the delivery tool to allow for penetration of the blood-brain barrier and to enhance anti-GBM specificity might be needed prior to advancing VLP(+Vpx) for clinical application. A recent study has shown that Vpx induces an innate immune response independent of SAMHD1 degradation [ 53 ], indicating a need for a careful evaluation of VLPs and Vpx activities prior to considering their use in clinical setting. On the promising side the tolerance of normal astrocytes to VLP(+Vpx) treatment shows a potentially lower effect on normal cells or tissue around the GBM.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the occurrence of cell death in THP-1 cells inoculated with high virus inputs accompanied by the induction of an antiviral IFN-stimulated gene (ISG) response [22]. In this study, we further characterize the cellular and viral determinants of this virus-induced cell death in monocytic cells upon HIV infection.…”
Section: Introductionmentioning
confidence: 87%
“…Plasmids, virus production and infection. HIV-1-GFP was produced by transfection of the NL43-based viral plasmid pHIV-CMV-GFP SIVp6 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26), which lacks env, nef and vpr genes, contains a 10 amino acid stretch from SIV p6 (for efficient Vpx packaging), and GFP expression is driven by a CMV promoter.…”
Section: Methodsmentioning
confidence: 99%